Teaching-learning methodologies in virtual education - Espinosa-Rodríguez, José (2022)
Learning is a continuous and diverse process that requires knowledge and competencies to face life and the challenges of the 21st century, which became more acute due to the health emergency caused by Covid-19. In this sense, the implementation of active methodologies in virtual learning environments (VLE) are a response to overcome the challenges presented in terms of the development of meaningful learning in non-face-to-face modalities and the innovation of pedagogical practice mediated by CT. Among the most commonly used methodologies in VLE are the case method, problem-based learning, project-based learning and the inverted classroom. In addition, there are techniques that allow "activating" learning moments, encouraging participation, collaborative work and the generation of content by students, thus favoring application over transmission of content. On the other hand, to effectively introduce ICT in the teaching-learning process through active methodologies involves transforming the educational practice from the change of roles (teacher and students) and their relationship with the digital domain, through the development of digital competencies. Finally, there are a large number of digital resources that can be used as part of active methodologies, whose objective will be to overcome the passive role of students and teachers as consumers of information, allowing them to adopt a more active role in the generation of new knowledge from the exchange with other web users.